Paroxetine Induced Akathisia: Necessity for Rational Use - Maryam Mousavi; Padideh Ghaeli; Fanak Fahimi (Journal of Pharmaceutical Care, 2019)
Rare cases of akathisia have been reported with paroxetine in the literature. However, accurate diagnosis for early treatment is important since untreated akathisia can result in poor patient’s compliance, treatment failure, aggressive or suicidal acts.